KARAKTERISTIK FISIK DAN SENSORI LIP BALM DENGAN PENAMBAHAN EKSTRAK KULIT BUAH NAGA (Hylocereus polyrhizus) DAN MINYAK ALPUKAT (Persea americana) SEBAGAI PELEMBAB BIBIR - Al Khasanah; Murhadi Murhadi; Sri Hidayati; Dewi Sartika (Jurnal Agroindustri Berkelanjutan, 2023)
Lip balm is a formulation that is applied to the lips to prevent dryness and protect against adverse environmental factors. In this study, lip balm was made from natural ingredients, dragon fruit peel extract and avocado oil, to determine the effect of dragon fruit peel concentration and avocado oil concentration as well as the effect of the interaction between dragon fruit peel concentration and avocado oil on its characteristics. lip balm. This research was carried out factorial in a Complete Randomized Block Design (RAKL) with 2 factors and 3 replications. The first factor is the concentration of dragon fruit peel (P) which consists of 4 levels (0%, 5%, 10% and 15%), and the second factor is the concentration of avocado oil (A) which consists of 4 levels. levels (0%, 5%, 10% and 15%). The data obtained in the analysis of variance were tested with the homogeneity test (Bartlett) and the adaptability test (Tuckey). The data were analyzed for variance using the OP (Orthogonal Polynomial) test at the 5% level. The research results showed that adding a concentration of dragon fruit peel extract had a very real influence on the characteristics of lip balm, and the best concentration used was 10%. The addition of avocado oil concentration has a significant effect on the lip balm features, and the best concentration is 10%. There is an interaction between the concentration of dragon fruit peel and the concentration of avocado oil in lip balm, where the addition of concentration has a very real influence on the texture, aroma, color, spreadability, overall acceptability, pH, melting point and the resulting results. The best treatment is P2A2 with a concentration of fruit peel extract. Dragon fruit 10% and avocado oil 10% which have an average texture score of 4,900 (smooth), color preference score of 4,883 (like), aroma 4,550 (like), spreadability 4,767 (like), overall acceptability 4,900 (like) and point melting 58,500 and pH 6,395.